Faecal indicator bacteria in New Zealand freshwater fish: a pilot study - Sarah Coxon; Jon S Harding; Brent Gilpin (New Zealand Journal of Marine and Freshwater Research, 2019)
Recent studies have suggested that poikilothermic animals, such as fish, may represent a previously overlooked source of the faecal indicator bacteria (FIB) used for the assessment of water quality. However, quantitative studies of FIB in poikilotherms are scarce. We investigated the presence of FIB in the faeces of five freshwater fish species. E. coli and enterococci were detected in 71 and 76% of faecal samples, respectively. Concentrations were highly variable, with maximum concentrations (2.1 × 10 4 E. coli and 1.3 × 10 6 enterococci per gram of faecal material) up to four orders of magnitude higher than present in the water column. FIB were not detected in faecal samples from marine fish. Our findings suggest that FIB ingested from the environment may be capable of replication within the fish gut, making fish a potential source and transport mechanism for FIB in New Zealand freshwaters. This may have implications for water quality monitoring.